Factors Related with Nurse Compliance in the Implementation of Patient Safety Indicators at Hospital - Taufik Alhidayah; Fransisca Sri Susilaningsih; Irman Somantri (Jurnal Keperawatan Indonesia, 2020)
Patient safety is one of the five crucial hospital safety issues. This study aimed to determine factors related with nurses’ compliance in the implementation of indicators of patient safety goals (IPSG 1, IPSG 2, IPSG 5, and IPSG 6). This study was a descriptive correlative with a cross-sectional approach. Samples were recruited using a purposive sampling technique (n = 102). Data were analyzed using chi-square and Mann–Whitney tests. The results of this study indicate that the leadership style of the head nurse, rewards, attitudes, and motivation had a significant relationship with the level of adherence in the implementation of IPSG 1 and IPSG 2. The level of nurses’ compliance in the implementation of IPSG 5 was only influenced by the leadership style of the room head and the nurses’ positive attitude. None of the factors had significant relationships with the level of nurses’ compliance in the implementation of IPSG 6. The consultative leadership style of the room head can change the level of nurses’ compliance in the implementation of IPSG 1 by 5.6 times, with 5.06 times toward IPSG 2 and 4.71 times toward IPSG 5. This research recommends the need for consultative leadership style from the room head to carry out the roles and functions as a supervisor to improve associate nurses’ compliance in the implementation of IPSG 1, IPSG 2, IPSG 5, and IPSG 6. Abstrak Faktor-Faktor yang Berhubungan dengan Tingkat Kepatuhan Perawat dalam Implementasi Indikator Sasaran Keselamatan Pasien di Rumah Sakit. Keselamatan pasien adalah salah satu dari lima isu penting keselamatan di rumah sakit. Penelitian ini bertujuan untuk menentukan faktor-faktor yang terkait dengan kepatuhan perawat dalam penerapan indikator sasaran keselamatan pasien (IPSG 1, IPSG 2, IPSG 5, dan IPSG 6). Desain penelitian menggunakan deskriptif korelatif dengan pendekatan cross-sectional. Sampel diambil dengan menggunakan teknik purposive sampling (n= 102). Data dianalisis dengan menggunakan uji Chi-square dan Mann-Whitney. Hasil penelitian menunjukkan bahwa gaya kepemimpinan kepala ruangan, penghargaan, sikap, dan motivasi memiliki hubungan yang signifikan dengan tingkat kepatuhan dalam penerapan IPSG 1 dan IPSG 2. Tingkat kepatuhan perawat dalam penerapan IPSG 5 hanya dipengaruhi oleh gaya kepemimpinan kepala ruangan dan sikap positif perawat. Tidak ada faktor yang memiliki hubungan signifikan dengan tingkat kepatuhan perawat dalam penerapan IPSG 6. Gaya kepemimpinan konsultatif kepala ruangan dapat mengubah tingkat kepatuhan perawat dalam penerapan IPSG 1 sebesar 5,6 kali, dengan 5,06 kali terhadap IPSG 2 dan 4,71 kali terhadap IPSG 5. Penelitian ini merekomendasikan perlunya gaya kepemimpinan konsultatif dari kepala ruangan untuk melaksanakan peran dan fungsi sebagai pengawas untuk meningkatkan kepatuhan perawat dalam penerapan IPSG 1, IPSG 2, IPSG 5, dan IPSG 6. Kata Kunci: indikator sasaran keselamatan pasien, kepatuhan, perawat